The Roles of Productive Assets Quality in Mediating Effect of Risk Management Implementation to the Firm Value in Indonesian Banking - Baroroh, Niswah (Jurnal Dinamika Akuntansi, 2016)
This study aims to examine the role of productive assets quality in mediating the effect of risk management implementation to the firm value. The population in this study was banking that went public in Indonesia in the year 2011-2013 as many as 31 companies. This study used quantitative approach with purposive sampling technique and obtained 53 samples that met the criteria. The analysis technique used path analysis with software tools SPSS 21. The results of this study indicated that the implementation of Risk Management and quality of productive assets did not affect the firm value. Risk Management also did not affect the quality of productive assets, and the quality of productive assets was not able to mediate the implementation of risk management to the firm value.